Self Disclosure Analysis of First Account and Second Account Users on Instagram among Students - Budiyanto, Revanni Nahari Aza; Aisyah, Vinisa Nurul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: The purpose of this research is to find out how the self-disclosure of first account and second account users on Instagram uses the Johari Window theory. Students who use Instagram not only have one account but have many accounts. Methodology: This type of research is qualitative research with the determination of informants using a purposive sampling technique. Data collection techniques using semi-structured interviews. Data validity uses data. Results: The results of this study are that in the self-disclosure process of Communication studies for students who use multiple accounts on Instagram, self-disclosure by students varies in each area. In the open area, students carry out self-disclosure including facial identity, happy feelings, and sharing daily life with their friends as students on the first account. In the hidden area, students hide their identity, name, profile photo, and private account to prevent others from finding the second account they have. In the blind area, students do not know other people's responses when they use a second account. while the unknown area is an area where the use of a second account is known by other people. Applications/Originality/Value: The researcher describes the social phenomena that exist among students regarding the self-disclosure of users of first accounts and second accounts on Instagram. This research has differences with other studies which lie in the research object, the social media use.